2014
DOI: 10.3109/08923973.2014.921690
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone inhibits production of proinflammatory mediators in response to lipopolysaccharideviainactivation of nuclear factor-κB

Abstract: The effect of spironolactone (SPIR) on lipopolysaccharide (LPS)-induced production of proinflammatory mediators was examined using RAW 264.7 macrophage-like cells and mouse peritoneal macrophages. SPIR significantly inhibited LPS-induced production of nitric oxide (NO), tumor necrosis factor-α and prostaglandin E2. The inhibition was not mediated by cell death. SPIR reduced the expression of an inducible NO synthase mRNA in response to LPS. SPIR significantly inhibited phosphorylation of p65 nuclear factor (NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Other anti-inflammatory agents beyond those already discussed have been studied in autism. Spironolactone is a potassium sparing diuretic and an anti-inflammatory which downregulates nuclear factor- κ B [ 24 ]. Bradstreet et al reported the first case of significant reduction in autism severity and improved expressive language after a short course of spironolactone [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other anti-inflammatory agents beyond those already discussed have been studied in autism. Spironolactone is a potassium sparing diuretic and an anti-inflammatory which downregulates nuclear factor- κ B [ 24 ]. Bradstreet et al reported the first case of significant reduction in autism severity and improved expressive language after a short course of spironolactone [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…MR antagonists are often used to treat hypertensive patients and have beneficial effects in patients with chronic heart failure and ischemic heart diseases[ 14 , 15 , 22 , 23 ]. Many recent investigations have demonstrated the beneficial effects of MR antagonists with respect to inflammatory responses and IRI in vitro and in vivo [ 6 - 13 ]. Kato et al[ 6 ] showed that SPL inhibits the production of pro-inflammatory mediators, such as TNF-α and nitric oxide, in response to lipopolysaccharides in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic and reperfusion injury (IRI) causes the release of numerous pro-inflammatory mediators, such as cytokines and nitric oxide, and results in multiple organ dysfunction (MOD), a leading cause of death in HS patients[ 1 - 5 ]. Mineralocorticoid receptor (MR) antagonists, such as spironolactone (SPL) and eplerenone (EP), have anti-inflammatory effects in vitro [ 6 - 8 ]. In particular, SPL inhibits inflammatory responses, such as the attenuation of cytokine and NF-kappa B responses, in vitro [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spironolactone is a synthetic 17-lactone steroid, belonging to the "potassium-sparing diuretics" class of drugs and is known as a competitive aldosterone antagonist [76] with potent anti-inflammatory, immunologic, and hormone-modifying properties [77][78][79][80]. Currently, this drug has been used for acne, hirsutism, and precocious puberty, demonstrating safety and tolerability.…”
Section: Spironolactonementioning
confidence: 99%